Análise de paralelismo para reconfiguração de redes de distribuição com geração distribuída usando software ATPDraw - Garcia, Ian Gabriel Brum (2015)
Improving Distribution Systems has been strongly driven by advances in automation and network data collection. This is reflected in improvements in quality of service and product, and reliability in service to consumers by the power companies, being made substantial investments in promotion of research and information technology. Be under normal conditions of operation or contingency, one of the techniques used in this sense is changing the topology of the networks. In normal operation conditions the main objectives are the reduction of technical losses, improvement in voltage levels and reliability indicators. The purpose of this work involves the verification of the technical feasibility of a methodology parallels distribution networks with distributed generation using ATPDraw software, allowing automatic load transfer in electrical systems. The advantage of placing in parallel feeders is to avoid the shutdown of consumers during a short period of time to perform the maneuvers. The most relevant contributions of this work are: general methodology for the parallels studies, contemplating the Distributed Generation; Simplified equivalent circuit in ATPDraw; application for automatic reconfiguration of distribution networks. The ability to represent themselves on the same platform transmission and distribution systems, analysis of electromagnetic transient, is another differential of this application. Case studies are used to applying the methodology using actual data from electric utilities, contemplating various operating conditions.